Enhanced Oxidation of Organic Contaminants by Mn(VII)/CaSO3 Under Environmentally Relevant Conditions: Performance and Mechanisms. (1st January 2021) - Rao, Dandan; Chen, Jie; Dong, Hongyu; Qiao, Junlian; Zhou, Baoxue; Sun, Yuankui; Guan, Xiaohong
Highlights: Mn(VII)/CaSO3 is better than Mn(VII)/Na2 SO3 for abating organics at pH ≥7.0. Much less residual Mn(II) was achieved by Mn(VII)/CaSO3 than by Mn(VII)/Na2 SO3 . Both radicals and Mn intermediates are involved in Mn(VII)/CaSO3 system. Excess S(IV) could quench radicals but did not greatly consume reactive Mn species. Slow release of S(IV) from CaSO3 alleviated the S(IV) quenching effect on radicals. Abstract: Although permanganate activation by sodium sulfite (Mn(VII)/Na2 SO3 ) has shown great potential for rapid abatement of organic contaminants, the limited reactivity under alkaline conditions and undesirable Mn residual may prevent its widespread application. To solve these challenges, calcium sulfite (CaSO3 ) was employed as a slow-release source of SO3 2− /HSO3 − (S(IV)) to activate Mn(VII) in this study. It was found that the application of CaSO3 solid could extend the effective working pH range of Mn(VII)/S(IV) from ≤7.0 to ≤9.0. Moreover, due to the enhanced precipitation of MnO2 with the presence of Ca 2+, very low Mn residual (<0.05 mg/L) was achieved in Mn(VII)/CaSO3 system. Mn(VII)/CaSO3 system is a unique two-stage oxidation process in terms of reaction kinetics and reactive oxidants. Specifically, Mn(VII) was rapidly consumed and reactive Mn intermediates (e.g., Mn(VI), Mn(V)), SO4 −, and HO were produced in the first stage. However, the second stage was governed by the interaction between MnO2 and S(IV), with SO4 − and HO serving as the dominant reactive oxidants. Taking advantage of an automatic titrator, excess S(IV) was found to greatly quench the generated radicals, whereas it did not cause a significant consumption of reactive Mn species. All these results improved our understanding of the Mn(VII)/S(IV) process and could thus facilitate its application. Graphical abstract: Image, graphical abstract